Loud music induced thresholds shifts and damage risk prediction - JAROSZEWSKI, A.; RAKOWSKI, A. (Archives of Acoustics, 1994)
Temporary thresholds shifts in musicians using high power electronic equipment were measured immediately after performance. The danger of permanent hearing loss is predicted on the ground of Damage Risk Criteria.